Road grip test in Arjeplog - Engström, Niclas; Andrén, Henrik; Nybacka, Mikael; Fransson, Lennart; Larsson, Roland (Luleå tekniska universitet, Maskinelement, 2008)
The Swedish road administration sees a need to improve the road grip estimation capacity for the Swedish road system. The challenge is to find methods to measure road grip fast and reliable. There where six different system types at the tests in Arjeplog, three continuous, two system measuring road grip through deceleration and one system based on GPS and accelerometers. Two system types used air craft runway tires. The other systems used either studded winter tires or friction winter tires. Test runs where performed and road grip where recorded for three different surface types, old system 2000 ice, polished ice and new system 2000 ice. Weather data was collected during the three days. It is clear that all systems can detect changes in road grip. It is clear that continuous systems hold an information advantage over the sequence oriented systems. For measurements of road grip on winter roads, we recommend that rubber compounds adapted for cold conditions are used, as the resolution of the road grip measurement where better. In extreme condition like on polished ice, studded winter tires increase the road grip significantly. Godkänd; 2008; 20081007 (ysko) Intelligenta inlandsvägen, CASTT - Centre for Automotive Systems Technologies and Testing